2011
DOI: 10.1093/dnares/dsr004
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific Typing of DNA Based on Palindrome Frequency Patterns

Abstract: DNA in its natural, double-stranded form may contain palindromes, sequences which read the same from either side because they are identical to their reverse complement on the sister strand. Short palindromes are underrepresented in all kinds of genomes. The frequency distribution of short palindromes exhibits more than twice the inter-species variance of non-palindromic sequences, which renders palindromes optimally suited for the typing of DNA. Here, we show that based on palindrome frequency, DNA sequences c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Importantly, some authors have in addition used higher-dimensional vectors of base composition patterns than simple nt counts. A major locus of activity has been in the use of multidimensional dinucleotide, trinucleotide and, most commonly, tetranucleotide composition vectors (4NCV; Teeling et al, 2004 ; Slater and Birney, 2005 ; Chatterji et al, 2007 ; Emmersen et al, 2007 ; Dick et al, 2009 ; Willner et al, 2009 ; Ghosh et al, 2011 ; Lamprea-Burgunder et al, 2011 ; Brisson et al, 2012 ; Saeed et al, 2012 ; Strous et al, 2012 ). Hexanucleotide counting has also been used to separate simple mixtures of a few species ( Hraber and Weller, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, some authors have in addition used higher-dimensional vectors of base composition patterns than simple nt counts. A major locus of activity has been in the use of multidimensional dinucleotide, trinucleotide and, most commonly, tetranucleotide composition vectors (4NCV; Teeling et al, 2004 ; Slater and Birney, 2005 ; Chatterji et al, 2007 ; Emmersen et al, 2007 ; Dick et al, 2009 ; Willner et al, 2009 ; Ghosh et al, 2011 ; Lamprea-Burgunder et al, 2011 ; Brisson et al, 2012 ; Saeed et al, 2012 ; Strous et al, 2012 ). Hexanucleotide counting has also been used to separate simple mixtures of a few species ( Hraber and Weller, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although palindromic motifs have been known to successfully differentiate chromosomes, as shown in [14]. However in Figure 19, we note that palindromes do not successfully recreate the taxonomy tree from Figure 14.…”
Section: Resultsmentioning
confidence: 92%
“…Since the spectrum set motifs were originally inspired from palindromic restriction sites, we also studied the proportions of an exhaustive list of length-6 palindromic motifs (64 in total) across the sequence data. Interestingly, although palindromic motifs have been known to successfully differentiate chromosomes, as shown in [ 14 ]. However in Figure 19 , we note that palindromes do not successfully recreate the taxonomy tree from Figure 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, a 16 ) with a i = f i . The introduction of this signature is motivated by a study where the frequency distribution of palindromic tetranucleotides was shown to exhibit highest inter-species but low intra-species variance on 10,000 bp sequences [40]. Combination Signature (ρ max , ρ min , ρ P ): As a combination of ρ max , ρ min and ρ P , it maps a sequence s to a vector (a 1 , .…”
Section: Genomic Signatures and Their Rationalementioning
confidence: 99%